АЗАМАТТЫҚ ҮРДІСТЕГІ АПЕЛЯЦИЯ ИНСТИТУТЫ (Journal of actual problems of jurisprudence, 2019)
The appeal one of two forms of the appeal in higher judicial instance of the decisions, verdicts, definitions and decisions of court in criminal andcivil process not entered in lawful force.